National evaluation of the new deal for communities programme: household survey data, 2002-2008 (UK Data Service, 2010)
The National Evaluation of the New Deal for Communities Programme (NDC) surveys began in 2002. To begin the programme, MORI Social Research worked with CRESR at Sheffield Hallam University, on behalf of the Neighbourhood Renewal Unit. The first phase of the programme took the form of a large-scale project comprising base-line household surveys in each of the 39 NDC areas in England in 2002, and follow-up interviews in 2004. The follow-up survey had a longitudinal element, combined with a new cross-sectional survey, and was designed to track changes over time (including direct changes), by following up residents who were interviewed in 2002, and also those who had moved out of NDC areas. The next survey in the NDC programme was conducted in 2006. In October 2005, Ipsos UK and MORI had combined to become Ipsos MORI. GfK NOP collaborated with Ipsos MORI Social Research Institute on the 2006 survey, as on previous waves (see documentation for further details). The fourth survey conducted among NDC residents was completed in 2008. The survey was designed to track change overtime, including direct change by following-up residents who were interviewed previously. A comparator survey was also undertaken in 2002, 2004, 2006 and 2008 for a sample of deprived wards in the same local authority districts as the NDCs, but not in wards bordering them. This national deprived area survey aimed to help understand how NDC areas differ from other deprived areas. Furthermore, following the design of the main survey, it aimed to identify differences in how these areas change over time, via follow-up and longitudinal surveys. A key aim of the evaluation survey is to help establish the degree to which change in NDC areas is unique, or whether it is mirrored elsewhere. Users should note that the comparator survey is described in the documentation, but has not yet been deposited at the UK Data Archive. Work was done with each of the 39 NDC area partnerships to design questions relevant to local issues, and to gauge level of awareness of projects. Ipsos MORI was also involved in a number of activities with the partnerships, designed to help them gain maximum value from the research at a local level. These included training local residents as interviewers to work on the survey, and a series of training sessions for partnerships. A survey 'extranet' site has also been established for partnerships, to encourage wider dissemination and use of the data.